Verified fuselage section water impact modelling. (October 2019) - Song, Y.; Horton, B.; Bayandor, J.
ABSTRACT: Along many flight corridors, bodies of water serve as preferred emergency landing options. Thus, relevant scenarios must be investigated to improve aircraft crashworthiness in the event of an impact landing on water. Enhancing the damage tolerance of aircraft structures through repetitive experiments can, however, prove highly uneconomical. Such large-scale trials can be influenced by many factors of uncertainty adversely affecting the quality of the results. Therefore, the work presented in this study focuses in particular on evaluating a computational methodology perfected for aircraft water ditching using Coupled Lagrangian-Eulerian (CLE) that allows detailed prediction of structural response of a verified deformable fuselage section during such events. Validation of the fluid-structure interactive (FSI) strategy developed is conducted, thoroughly comparing the method against the analytical and experimental results of multiple wedge drop tests. Finally, the validated FSI strategy is applied to a high-fidelity fuselage section model impacting water to simulate and assess a realistic ditching scenario.